A descriptive study to assess the knowledge and utilization of Ayushman Bharat Pradhan Mantri Arogya Yojana [ABPMJAY] among vulnerable population in a selected Rural community, Gurugram - Ms Soniya; Mr Lakshya; Mr Aadil; Ms Aarti; Ms KM Sonam (The Bioscan, 2025)
Background: Health is a fundamental human right, and ensuring its accessibility and affordability is crucial for all segments of society. In India, a large proportion of the population, particularly in rural areas, continues to face challenges in accessing quality healthcare due to financial constraints. To address this, the Government of India launched the Ayushman Bharat Pradhan Mantri Jan Arogya Yojana (AB-PMJAY)—a flagship health insurance scheme aimed at providing financial protection and accessible healthcare services to over 10.74 crore poor and vulnerable families. Objective: a) To assess the knowledge and utilization of Ayushman Bharat Pradhan Mantri Jan Arogya Yojana [ABPMJAY] among vulnerable population in a selected rural community, Gurugram. b) To seek association between knowledge score with their selected demographic variable. Methodology: In the present study Quantitative Research approach with descriptive research design was adopted. Total 130 Vulnerable population were selected by using simple random sampling. The tools used for data collection were a) structured interview schedule for demographic data, b) Knowledge questionnaires, c) Checklist to assess the utilization of Ayushman Bharat Pradhan Mantri Jan Arogya Yojana [ABPMJAY] Result: In knowledge area mean score in 10.10 with mean percentage 67.33% and SD 2.489. Most participants (74.6%) have adequate knowledge, while 25.4% have inadequate knowledge. This suggests that a significant portion of the sample is well-informed. In the utilization 58.5% of participants have availed the AB-PMJAY scheme in the past year, 50% of participants report having to spend additional amounts despite using the scheme, 53.8% of participants have availed free medicines under the scheme, A majority of 63.1% believe that the scheme covers pre-existing diseases, 42.3% have utilized AB-PMJAY services for surgery, daycare treatment, hospitalization, vaccinations, and medicines, Only 20% have used the scheme for dental treatments, 51.5% have availed cashless services for any illness, A smaller percentage, 23.1%, have used the scheme for maternity services, 28.5% have availed services like dialysis, chemotherapy, radiotherapy, physiotherapy, and oxygen therapy, Lastly, 29.2% have utilized diagnostic services under the scheme. Conclusion: Study concludes that while a majority of the vulnerable population in the selected rural area of Gurugram possesses adequate knowledge about the Ayushman Bharat Pradhan Mantri Jan Arogya Yojana (AB-PMJAY), the actual utilization of the scheme remains moderate. Furthermore, the study found no significant association between knowledge levels and demographic variables, suggesting that other factors may influence utilization. These insights highlight the need for continuous community-level awareness programs, improved service delivery mechanisms, and policy adjustments to enhance the effectiveness and reach of AB-PMJAY among the rural poor. KEYWORDS Ayushman Bharat Pradhan Mantri Arogya Yojana [ABPMJAY], vulnerable population.